Solitaire Stent Reduced Disability in Stroke Patients in the SWIFT PRIME Trial. Issue 2 (11th March 2015) - Zarifyan, Alla
The SWIFT PRIME study demonstrated that the Solitaire stent was safe and effective at reducing poststroke disability in patients with acute ischemic stroke. Functional independence (mRS of 0 to 2) at 90 days was achieved in 60.2% of patients in the Solitaire plus IV tPA group vs 35.5% in the IV tPA group ( P < .0008).